An Exploratory Factor Analysis of the Strategy Inventory for Language Learning (SILL) in Ukrainian Philology Students - Joseph Kush; Alla Krasulia (Naifaderu Cipta Sejahtera, 2025)
Purpose This study examines the factor structure of the Strategy Inventory for Language Learning (SILL) in a sample of English- and Ukrainian-speaking, Ukrainian college students. There is abundant research supporting the pedagogical belief that the use of learning strategies by second language learners is strongly associated with language learning success. Worldwide, the SILL is the most popular instrument that assesses these skills; however, studies evaluating the psychometric properties of the scale have offered mixed results. Methodology This study used exploratory factor analysis (EFA) to examine the factor structure of the SILL with a sample of 193 Philology students enrolled in a large university in northeastern Ukraine. Results/Findings Our modification of the 50-item SILL resulted in a condensed, 38-item, two-factor revision of the scale which was more psychometrically defensible for the assessment of second language learner characteristics. To reflect the more psychometrically-sound revision, the modified scale is called the SILL-KK. Results of our study failed to find support for the original six-factor structure put forward by Oxford and instead found the data best characterized by a two-factor model. Our refinement of Oxford’s 50-item SILL resulted in an abbreviated, 38-item, two-factor version of the instrument Implications First, this study addresses criticisms of the dearth of SILL psychometric validation research. Second, the study responds to some theoretical concerns raised in the literature regarding strategy category overlap. From a practical standpoint, the SILL-KK will hopefully lead to more accurate diagnoses of language learning strategies for both students and instructors in addition to the design and development of better individualized instructional materials.